IoT based stir casting system of aluminium MMC. (2021) - Raj, P. Anantha Christu; Kavitha, P.; Sophia, S.; Thilagam, K.; Devi, V.; Khan, J. Mohammed Feros
Abstract: In present days, an Internet of Things (IoT) based smart industry was established for casting sections that produces the different components in automobile, construction, railways and shipping. The effect of casting parameters and their performances on quality were analyzed through collected data from the system. A monitoring system has been introduced in every sector but the collected data are not being utilized properly. Hence, it is essential to set up a system suitable for the casting through IoT. In this paper, stir casting process was processed under IoT. Stir casting parameter and data were analyzed through IoT. It is expected that a process of efficient completion to be offered to the casting industries that desire to construct smart casting divisions in the future. The microcontroller, network and sensors have been used to improve the stir casting process. IoT based stir casting experimental investigation has been conducted on Aluminium Metal Matrix Composite (Al-MMC).